"I know you're kidding": Relationship closeness enhances positive perceptions of teasing. Issue 2 (22nd March 2015) - GORMAN, GLEN; JORDAN, CHRISTIAN H.
Abstract Feeling close in a relationship may enhance perceptions of teasing within that relationship. In Study 1, participants recalled instances of teasing—as both teaser and target—in close and nonclose relationships. Participants perceived teases in close relationships more positively and better intentioned than those in nonclose relationships, as both teaser and target. The discrepancy between teasers and targets in perceptions of intent was also reduced by felt closeness. In Study 2, interaction partner closeness was manipulated and a tease was staged. Teases delivered by a close (vs. nonclose) partner were perceived as more positive and better intentioned. Each study has limitations but their methods complement each other. Together they provide convergent evidence that relationship closeness increases positive perceptions of teasing.